PENDIDIKAN MULTIKULTURAL ADALAH MASALAH SOSIAL - Nurniswah Nurniswah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2013)
Indonesia, like other developing countries have social problems that are not simple. Even the most horrible, Indonesia experienced a prolonged crisis. The economic crisis that followed by other crises, we are aware of the importance of social capital. Social capital is the collective energy of the community in the form of togetherness, solidarity, cooperation, tolerance, trust, and responsibility of each member of the community in playing any role mandated. When energy is destroyed then destroyed also the collective harmony, balance, harmony, and harmony in society. Conditions were very pluralistic Indonesian society both from the aspect of ethnicity, race, religion and social status contribute to the development and the extraordinary dynamics of the community. It was considered very important to give a portion of multicultural education in the education system in Indonesia either through substance and learning models. It is considered necessary to provide debriefing and assist in the development of thought and personality insights and sensitivity training learners in dealing with the symptoms and social problems that occur in the social community.